Individual Preferences, Monetary Gambles, and Stock Market Participation: A Case for Narrow Framing - Barberis, Nicholas; Huang, Ming; Thaler, Richard H (American Economic Review, 2006)
We argue that “narrow framing,” whereby an agent who is offered a new gamble evaluates that gamble in isolation, may be a more important feature of decision-making than previously realized. Our starting point is the evidence that people are often averse to a small, independent gamble, even when the gamble is actuarially favorable. We find that a surprisingly wide range of utility functions, including many nonexpected utility specifications, have trouble explaining this evidence, but that this difficulty can be overcome by allowing for narrow framing. Our analysis makes predictions as to what kinds of preferences can most easily address the stock market participation puzzle.